Perkembangan ilmu perubatan: sebelum dan selepas kedatangan islam - Nizaita Omar (Universiti Kebangsaan Malaysia, 2006)
Nowadays,human beings are well-exposed with new experience in many fields of life regardless of its positive or negative impacts. Among those new experiences is in field of medicine. This experience is not limited to a community but extended to all communities in the world since ancient times. Islam is a comprehensive religion than emphasizes more on this field as well as provides certain laws including discussion on ethics carried out by patients and physicians. This article will briefly discuss the field of medicine particularly on its historical development